Peradaban Islam Rasulullah Periode Mekkah (622-632): Fondasi Awal dalam Sejarah Perkembangan Islam - Raskita Mega Wati Br.Pinem; Siti Aisyah; Fiza Ikramullah Lubis; Siti Nur Ainun; Shirajul Fuadi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the development of Islamic civilization during the time of the Prophet Muhammad (peace be upon him) using an approach that rejects the conceptual dichotomy between the Meccan and Medina phases. The title